Omega-3 Fatty Acids and Brainpower: The Role of Seafood Consumption - Ajit Pal Singh; Rahul Saxena; Suyash Saxena (International Journal of Brain Sciences, 2025)
The following article talks about the strong link between eating seafood and brain health, focusing on the role of omega-3 fatty acids, especially eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), in supporting brain development, function, and longevity. The article uses new research to show how these important polyunsaturated fatty acids help the brain in ways like memory, learning, focus, and attention. It also reduces the chance of developing dementia, Alzheimer's, and other neurological diseases. Better mood control and better sleep, both crucial for overall brain health, are also associated with omega-3s. Some of the best places to get EPA and DHA are from fatty fish, like mackerel, tuna, salmon, and sardines. Concerns about environmental pollutants, particularly mercury, are also prevalent. The article provides evidence-based guidance on selecting low-mercury fish, such as wild Alaskan salmon and sardines. Because environmental worries are growing, it stresses how important it is to choose sustainable seafood and supports responsible sourcing to protect marine ecosystems and human health for future generations. The piece stresses the importance of sustainable seafood in protecting our oceans and our health by encouraging people to eat in a way that is beneficial for the environment.
Keywords: Effects; Health; fatty acids; memory; research